Influences in fertility decisions among HIV-infected individuals in Lilongwe, Malawi: a qualitative study. Issue 3 (16th June 2016) - Haddad, Lisa B; Hoagland, Alexandra B; Andes, Karen L; Samala, Bernadette; Feldacker, Caryl; Chikaphupha, Kingsley; Tweya, Hannock; Chiwoko, Jane; Kachale, Fannie; Jamieson, Denise J; Phiri, Sam
Abstract : Background: The motivation to have a child may be complex with numerous influencing factors, particularly among individuals living with HIV. This study sought to understand factors influencing fertility decision-making for HIV-infected men and women in Lilongwe, Malawi. Methods: Thirteen focus groups were conducted among HIV-infected individuals enrolled in antiretroviral treatment services. Results: Participants identified a hierarchy of influences in fertility decisions including the importance of childbearing, patriarchal influence, family influences and concern regarding HIV transmission. Conclusions: Addressing fertility conversations beyond the confines of a relationship may be important, as family plays a significant role in fertility choices. Childbearing remains a fundamental desire among many individuals with HIV; however, concerns regarding transmission risk need to be addressed with efforts made to overcome misconception and assist individuals in balancing what may be competing influences.